Performance evaluation of Proton Waja car air conditioning system - Mohamad Nadzif, Zahirudin (2009)
Air conditioning is a process by which air is cooled or heated, cleaned or filtered, and circulated or recirculated. Air conditioning had become a standard option on most vehicle for enhancing comfort and safety. Regarding to this situation, an experiment and analysis need to be done to analyze the coefficient of performance (COP) of Proton Waja car during variable compressor speed and variable refrigerant weight. There are four locations of temperature measurement were selected in order to analyze the system. These locations are at the inlet and outlet of the compressor, the outlet of the condenser, and the inlet of the evaporator, respectively. The pressure was measured at the low pressure side and high pressure side which are at the outlet of the evaporator and inlet of the condenser, respectively. Before experimenting, a Statistica Software was used to reduce the error of experiment, and this software can design the experiment order. Besides that, the result from manual calculation can be validate with the result from Statistica Software. All of the parameters are measured during the cycle and were analyzed by using the properties table for refrigerant-134a and the p-h diagram for refrigerant-134a in order to determine the heat rejection, cooling effect, work of compressor and the coefficient of performance (COP) of the air conditioning system. The heat rejection, cooling effect, work of compressor, and the COP of the air conditioning system were investigated at variable speed of compressor and variable weight of refrigerant. The COP of the system was decreasing as the increasing of time and the compressor speed. It is also similar to COP of the system during the increasing of refrigerant weight and time in other experiment.